Settlement of Minor Criminal Offenses Under Aceh Qanun Number 9 of 2008 Concerning the Development of Customary Life and Traditions in Aceh - Hidayat, Arief Pandu; Fazzan , Fazzan; Nur, Muhammad; Rahmah, Siti; Zul 'Aidy, Zul 'Aidy (LOCUS MEDIA PUBLISHING, 2025)
Aceh Qanun Number 9 of 2008 on the Development of Customary Life and Traditions serves as a legal foundation for Acehnese society in resolving minor criminal offenses through customary mechanisms at the gampong (village) level. This qanun explicitly regulates 18 categories of cases that may be settled through customary institutions, thereby reflecting the vitality of customary law as an instrument for resolving social conflicts in line with Islamic values, justice, and local wisdom. However, in practice, the implementation of this qanun still encounters various challenges that require further examination. This study employs a juridical-empirical approach with the research site located in Blang Bintang Subdistrict. Data were collected through interviews with gampong officials, customary leaders, and relevant authorities, complemented by a review of regulatory documents, including Circular Letters issued by the Governor of Aceh, the Aceh Customary Council (MAA), and the Aceh Regional Police Chief, which reinforce the implementation of Qanun Number 9 of 2008. The analysis was conducted qualitatively, integrating perspectives from positive law, customary law, and Islamic law. The findings reveal that the mechanism for resolving minor criminal offenses at the gampong level has been carried out in accordance with Qanun Number 9 of 2008, particularly through deliberation and restorative approaches. Nonetheless, several obstacles persist, including limited understanding among gampong officials, external intervention by formal law enforcement, as well as weak documentation and supporting facilities. These conditions create challenges in realizing the legitimacy of customary law within the national legal system. To overcome these obstacles, it is necessary to strengthen customary institutions through training, the formulation of technical guidelines, and enhanced coordination between gampong authorities, the Aceh Customary Council, and law enforcement agencies. Regulatory and institutional support will further consolidate the role of customary law as a mechanism for resolving minor offenses in Aceh. Overall, Aceh Qanun Number 9 of 2008 has proven effective in the settlement of minor offenses, although its implementation still faces challenges. Strengthening customary institutions constitutes a strategic effort to reinforce the role of customary law within the framework of the national legal system.